Strengthening HIV Education and Health Promotion in Schools: A Case Study of ‘Aisyiyah Junior High School Bantul, Indonesia - Dhesi Ari Astuti; Muhamad Saleh; Nurul Kurniati; Siti Fatimah; Cindy Putri Febrianti; Khoirunnisah Hasibuan (GHMJ (Global Health Management Journal))
Background: Adolescents are a strategic target in preventing HIV/AIDS and drug abuse. The number of incidences of HIV among children aged 1–14 years has reached 14,150 cases. This number is increased by 700–1,000 each year. In the future, teenagers have the potential to spread information and conducive change, leading society toward a healthier paradigm dealing with HIV/AIDS and drugs.